Transformer-Based Design Techniques for Oscillators and Frequency Dividers - Luong, Howard Cam; Yin, Jun (Springer International Publishing : Imprint: Springer, 2016)
This book provides in-depth coverage of transformer-based design techniques that enable CMOS oscillators and frequency dividers to achieve state-of-the-art performance.  Design, optimization, and measured performance of oscillators and frequency dividers for different applications are discussed in detail, focusing on not only ultra-low supply voltage but also ultra-wide frequency tuning range and locking range.  This book will be an invaluable reference for anyone working or interested in CMOS radio-frequency or mm-Wave integrated circuits and systems.